Emodin and physcion alleviate cholestatic liver injury by targeting FXR: hepatoprotective components identified in processed Polygonum multiflorum Thunb. using a comprehensive two-dimensional biochromatography system - Li, Zhihui; Gu, Yanqiu; Yang, Jianbo; Wang, Shaozhan; Li, Shengnan; Chen, Panpan; Yao, Ru; Liu, Fangbin; Wang, Ying; Wang, Rong; Yuan, Yongfang (Frontiers in Pharmacology, 2025)
IntroductionPolygonum multiflorum Thunb. (PM) is a representative traditional Chinese medicine (TCM) that exerts different effects in raw and processed forms. The hepatotoxicity of PM is markedly reduced after processing, whereas its hepatoprotective effects are enhanced.PurposeThis study aimed to establish a novel comprehensive two-dimensional (2D) biochromatography system based on farnesoid X receptor (FXR), which is an important target in cholestatic liver injury (CLI), to investigate the material basis and mechanisms underlying the enhanced hepatoprotection and reduced hepatotoxicity of processed PM (P-PM).MethodsA comprehensive 2D FXR biochromatography system was established by immobilizing FXR on 3-mercaptopropyltrimethoxysilane (MPTS)-modified silica gel. This system was used to identify the FXR-binding components in raw PM (R-PM) and P-PM. Molecular docking, surface plasmon resonance, and frontal affinity chromatography were used to validate the interactions. The hepatoprotective effects of emodin and physcion were assessed in α-naphthylisothiocyanate (ANIT)-induced CLI mouse models, and an FXR antagonist (Z-guggulsterone) rescue experiment was performed. The expression of FXR signaling-related proteins, including FXR, small heterodimer partner (SHP), bile salt export pump (BSEP), Na+-taurocholate cotransporting polypeptide (NTCP), and inflammatory cytokines, was assessed by Western blotting, real-time quantitative reverse transcription PCR, and immunofluorescence.ResultsThe comprehensive 2D FXR biochromatography system successfully identified emodin and physcion as key FXR-binding components, with significantly increased content in P-PM. These components may contribute to the enhanced hepatoprotection and reduced hepatotoxicity of P-PM. In vivo, emodin and physcion alleviated ANIT-induced CLI, as evidenced by improved histopathological features and decreased serum levels of liver function markers. Mechanistically, both components upregulated the expression of FXR, BSEP, SHP, and NTCP while suppressing inflammatory cytokine expression. Their hepatoprotective effects and FXR-related upregulation could be disrupted by FXR antagonist Z-guggulsterone. These results suggest that emodin and physcion are key components contributing to the hepatoprotective effects of P-PM, likely through activation of the FXR signaling pathway and suppression of inflammation.ConclusionThis study established a novel, efficient, rapid, and accurate comprehensive 2D FXR biochromatography system, which is suitable for screening targeted components in TCM, and can be extended to research on other TCMs.